Structural response and performance of hexagonal thin-walled grooved tubes under dynamic impact loading conditions. (15th July 2018) - Isaac, Chukwuemeke William; Oluwole, Oluleke
Highlights: Obtaining the crashworthiness parameters of hexagonal thin-walled grooved tubes. Axial and oblique impact responses of hexagonal grooved tubes under dynamic loading. Hexagonal grooved tubes – a good candidate used as energy absorbers. Abstract: This paper numerically investigates the structural response and crashworthiness performance of a hexagonal thin-walled grooved tube subjected to axial and oblique impact loading conditions. First, an analytical formulation that estimates the mean crushing force and total energy absorption are obtained for both hexagonal and circular tubes subjected to high dynamic impact loading conditions. The solutions of the analytical model are used to verify and compare the approximate solutions of the finite element model. The inclusion of grooves to the conventional hexagonal thin-walled tubes shows the great potential for improving the crashworthiness performance such as the energy absorption capacity, crushing force efficiency and specific energy absorption. In further, parametric studies are performed, deformation modes of different models are obtained and their crushing force-displacement characteristics are described. The improved crashworthiness performance of the hexagonal thin-walled grooved tubes make them good candidate used as energy absorbers.